Feasibility for developing cardiovascular exercise recommendations for persons with motor-complete paraplegia based on manual wheelchair propulsion; A protocol and preliminary data. (2nd January 2016) - McCormick, Zachary L.; Lynch, Meaghan; Liem, Brian; Jacobs, Geneva; Hwang, Peter; Hornby, Thomas George; Rydberg, Leslie; Roth, Elliot
Abstract : Background : The Center for Disease Control, American Heart Association, and American College of Sports Medicine recommendations for duration and intensity of exercise are based on the amount of energy expenditure required to maintain cardiovascular health in able body individuals; 1000 Kilocalories (Kcals) per week of energy expenditure has been demonstrated to achieve this effect. Manual wheelchair propulsion (MWP) represents a practical and accessible form of exercise for individuals with paraplegia. Objective : To describe a method to determine the duration of MWP required to expend 1000 Kcals, when performed by individuals with paraplegia due to motor-complete spinal cord injury (SCI). Study Design : Cross-sectional study. Setting : Rehabilitation Research Laboratory. Participants : Sixteen adults with motor complete T3-T12 paraplegia (body mass index < 35, duration of paraplegia > 3 months). Interventions : Not applicable. Main Outcome Measures : Indirect calorimetry during MWP was measured in order to calculate caloric expenditure per minute. These data were used to calculate the number of minutes of MWP required to expend 1000 Kcal in one week. Results : During MWP, participants expended 3.3 ± 1.0 Kcal/minute. Based on this figure, 1000 Kcal of energy expenditure in one week would require 303 minutes of MWP per week, or 43.3 minutes per day, 7 days per week. Conclusions : Our data suggest that it is feasible to create a practical and accessible exercise recommendation based on manual wheelchair propulsion for individuals with paraplegia due to motor-complete SCI. Larger studies are needed in order to develop accurate exercise recommendations for persons with SCI.